Validity and reliability of the Very Short form of the Physical Self-Inventory among Turkish adolescents - AŞÇI, FEVZİYE HÜLYA (TAYLOR & FRANCIS LTD, 2017)
The study aimed to test the validity and reliability of the Very Short form of the Physical Self-Inventory (PSI-VS) among a sample of 635 Turkish adolescents. These adolescents have completed the 12 original items of the PSI-VS, plus a positively worded reformulation of the single reverse-keyed item of the physical attractiveness subscale. A series of confirmatory factor analyses was used to examine the psychometric properties of the original and modified versions of the PSI-VS. Findings revealed superior psychometric properties with the modified version than with the original set of items. The modified version was thus subsequently used to examine its factor structure invariance across sexes, age groups and sport practice involvement. Results not only report that this version was fully invariant across, but also that latent means were significantly different across sexes and sport practice involvement. In sum, the Turkish modified version of the PSI-VS presents acceptable psychometric properties and may be used to repeatedly and/or intensively assess participants' physical self-perceptions in the context of sport and exercise interventions.
Keywords: Age; sex; measurement; invariance; PSI-VS; Turkish; GOODNESS-OF-FIT; DESCRIPTION QUESTIONNAIRE; PERCEPTION PROFILE; INVARIANCE; INDEXES; CRITERIA; FRENCH